Pengaruh Durasi Kangaroo Mother Care Terhadap Neonatus Outcome Pada Bayi Berat Badan Lahir Rendah (BBLR) - Siti Na'imah; Dwi Agustiana Sari; Chrisna Wijaya (Jurnal Indonesia Sehat, 2024)
Background: Low birth weight is defined as a baby’s birth weight of less than 2500 grams. One method that is able to meet the needs of  Low birth weight  babies with the kangaroo mother care (KMC) method, which is a method that is made direct contact between the baby's skin and the mother's skin (skin to skin contact) and puts the baby in the area.KMC has benefits for increasing vital signs and weight of Low birth weight of infant. Objective:  To determine the effect of kangaroo mother care treatment on the vital signs and weight of Low birth weight of infant. Method: The type of research design is pre-experimental. The population is Low birth weight of infant. The sample amounted to 30 respondents, with purposive sampling. The research instrument used an observation was carried out for 4 consecutive days. Univariate and bivariate data analysis techniques for non-parametric tests are the Friedman test. Results: There is an increase in body temperature by 0. 41 C with p = 0.001, heart rate frequency increased the highest average value on day 4 measurement was 23.77x / minute with p-value 0.00, infant breathing increased every day with a p-value of 0.01, a significant increase in saturation value was highest on day 4 measurement with a difference of 1.60 value and it was found that p-value 0.01, significant weight increase on day 4 measurement with p-value. Conclusion:  This study proves that there is an influence of the duration of Kangaroo Mother Care towards neonatal outcomes in low birth weight (LBW) babies.